Référendum d’avril 1972 : l’Europe française des débuts de la décennie - Lafleur, Guy-Antoine (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1978)
Using a method of content analysis which has been elaborated specifically to that end, this research analyses the perception of the French political parties with regard to Europe, the European institutions and the European integration process in general. The data selected to that end were the speeches pronounced during the French referendum on Europe held in April 1972. The main conclusion of this comparative analysis is to the effect that the image that the French political parties have presented of Europe and of the European institutions at that time, was altogether a rather abstract, idealist and descriptive one, which did not emphasize the necessity for further integration.